Collaborative diabetes training in outpatient primary care - Tiina Tervaskanto-Mäentausta; Anja Taanila; Olavi Ukkola; Leila Mikkilä; Jari Jokinen; Essi Varkki (Journal of European CME, 2017)
Two Universities from Oulu, Finland organised integrated and interprofessional (IP) type 2 diabetes training periods for undergraduate medical and nursing students in collaboration with the University Hospital and Health and Wellbeing Centre of Oulu. There is an ongoing health, social services and regional government reform in Finland. The services will be organised in a customer-orientated way and the reform will combine the primary and secondary services. The training was tailored to reflect the real life future setting in Finnish primary care, and this model fits well with the principles of collaborative education. The study aimed at investigating students’ attitudes and readiness for inter professional learning and their learning experience in combined primary and secondary care settings. The second aim was to strengthen students’ professional skills by working with patients in a patient-centred manner. The “Readiness for Interprofessional Learning Scale” was used with added questions about pair training. Students’ perceptions of their clinical skills were evaluated. The students valued the mutual learning experience in outpatient primary care. They felt comfortable with working together and complemented each other. Students performed well with IP competencies such as patient centredness, communication and team functioning. Patients in general were very satisfied with the visit. Teamwork and collaboration, professional identity and pair work were highly scored in both student groups while roles and responsibilities were evaluated a little less positively. Collaboration between different levels of care and health policies is important when developing health professionals’ education. This IP teamwork experience helps both future and current health-care professionals to better organise the care of chronic illnesses.